An effective encapsulation for perovskite solar cells based on building-integrated photovoltaics. Issue 23 (30th May 2022) - Wei, Qi; Huo, Xiaonan; Fu, Qiang; Wang, Ting; Zhao, Heming; Wang, Yixuan; Yang, Jiansong; Zhan, Siqi; Zhou, Liang; Wang, Shiwei; Yin, Penggang
Abstract : An acrylate hot melt adhesive (AHMA) was synthesized and used in perovskite photovoltaic building integrated encapsulation. The excellent impact resistance and lead leakage prevented of the encapsulation structure has been confirmed. Abstract : The photoelectric conversion efficiency of lead-based halide perovskite photovoltaic cells (PSC) has reached 25% in recent years, which is the commercial level. A safe and environment-friendly encapsulation material and process for PSC determines its application in building-integrated photovoltaics. In this work, an acrylate hot melt adhesive (AHMA) with good transparency and extensive cohesiveness was obtained by free-radical copolymerization, based on which, the safety sandwich perovskite photovoltaic cell was prepared together with PVB film at 80 °C. It avoids the structural damage of perovskite devices under high-temperature or UV curing. Before and after packaging, 21.58% and 20.88% of the PCE were achieved, respectively, for the perovskite photovoltaic device, which shows good stability. It has been confirmed that more than 96% of lead leakage can still be blocked from the seriously damaged device after heavy rainfall for 6 hours. The encapsulation scheme introduced here is especially suitable for perovskite photovoltaic building integration.